Teacher experience of intercultural group work in higher education: A scoping review - Bergman, Becky; Van Maele, Jan; Spencer-Oatey, Helen; Negretti, Raffaella (Nordic Journal of Comparative and International Education (NJCIE), 2025)
One strategy to reach international goals at universities is intercultural group work (IGW), combining students from different cultural backgrounds to develop their intercultural skills and understanding. Much of the existing IGW research has had a student perspective, underscoring both affordances and challenges. To gain a more complete picture of IGW, this scoping review investigates the existing empirical literature on the teacher perspective. Our review shows scarce research in this area, mostly on virtual group work and individual course initiatives. A thematic analysis reveals that teachers’ focus in IGW is on facilitating interaction between student groups; planning the curriculum regarding learning outcomes, developing activities and assessment for IGW; and building intercultural competence. Teachers’ challenges with IGW also emerge such as lack of time, skills and training. We conclude that further research is needed about on-campus IGW, specifically how individual course initiatives might address program and institutional goals and become more sustainable.